Computer Science for All? The Impact of High School Computer Science Courses on College Majors and Earnings - Jing Liu; Cameron Conrad; David Blazar (Institute of Labor Economics (IZA), 2024)
This study provides the first causal analysis of the impact of expanding Computer Science (CS) education in U.S. K-12 schools on students' choice of college major and early career outcomes. Utilizing rich longitudinal data from Maryland, we exploit variation from the staggered rollout of CS course offerings across high schools. Our findings suggest that taking a CS course increases students' likelihood of declaring a CS major by 10 percentage points and receiving a CS BA degree by 5 percentage points. Additionally, access to CS coursework raises students' likelihood of being employed and early career earnings. Notably, students who are female, low socioeconomic status, or Black experience larger benefits in terms of CS degree attainment and earnings. However, the lower take-up rates of these groups in CS courses highlight a pressing need for targeted efforts to enhance their participation as policymakers continue to expand CS curricula in K-12 education.
Keywords: I23; J24; H52; 330; computer science; STEM; high school curricula; college major choice; earnings